Merlin, the product of NF2 gene, is associated with aromatase expression and estrogen formation in human liver tissues and liver cancer cells. Issue 172 (September 2017) - Cocciadiferro, Letizia; Miceli, Vitale; Granata, Orazia M.; Carruba, Giuseppe
Graphical abstract: Highlights: Aromatase is higher in HCC, intermediate in cirrhotic and low in nontumoral liver. Equivalent expression patterns of ERα36, AREG, ADAM17 and Merlin were seen. Estradiol increases AREG and decreases Merlin expression in liver cancer cells. Alteration of estrogen/Merlin activity and stem cell differentiation may lead to HCC. Abstract: The product of neurofibromatosis type 2 (NF2) gene, also known as Merlin/neurofibromin 2, homeostatically regulates liver stem cells by controlling abundance and signaling of epidermal growth factor receptor (EGFR), with a mechanism independent of the Hippo pathway. We have reported that locally elevated estrogen formation, driven by abnormally high expression and function of aromatase, may be implicated in development and progression of human hepatocellular carcinoma (HCC) through activation of a rapid signaling pathway mediated by amphiregulin (AREG) and EGFR. We have recently presented a model by which the aromatase-estrogen-amphiregulin-EGFR axis is activated in response to tissue injury and/or inflammatory disease, with its alteration eventually leading to development of major human tumors (liver, breast, prostate) and other chronic diseases (diabetes, obesity, Alzheimer's and heart disease). In this study, we investigated NF2 expression in liver cancer cells and tissues in relation to aromatase expression/function, estrogen receptor (ER) status and amphiregulin. Our data indicate that NF2 expression is associated with aromatase and AREG expression, being elevated in HCC tissues and HepG2 cells, intermediate in cirrhotic tissues and Huh7 cells, and lower in nontumoral liver and HA22T cells. In addition, NF2 expression is inversely related to wild type hERα66 and proportional to the expression of the membrane-associated hERα36 splice variant, as measured by exon-specific RT-PCR analysis, both in vivo and in vitro . Furthermore, incubation with estradiol induced a significant decrease of NF2 expression in both HA22T and Huh7 cells (over 54% and 22%, respectively), while no change could be observed in HepG2 cells, this effect being inversely related to aromatase expression and activity in HCC cell lines. Based on the above combined evidence, we hypothesize that NF2 behaves as a protein sensing tissue damage and aromatase-driven local estrogen formation, eventually leading to regulation of stem cells differentiation and tissue repair.